Estudo das rotas de formação, transporte e consumo dos gases metano e sulfeto de hidrogênio resultantes do tratamento de esgoto doméstico em reatores UASB - Claudio Leite de Souza (2010)
This study aimed at evaluating the processes of formation, movement, release andbconsumption of methane and hydrogen sulfide, generated during the treatment of domestic wastewater in UASB reactors, inside the reactor and at hydraulic structures close to it. The experiments were carried out in four UASB reactors, three in pilot scale (360 L) and one indemonstration scale (14 m3). The sampling points were strategically defined for the liquid and gaseous phases, as means of allowing the monitoring of the main parameters of interest, such as methane and sulfide dissolved in the liquid phase, methane and sulfide released to gas phase (biogas and waste gas), among others. The results allowed to conclude that the concentrations of dissolved methane and sulfide in the effluent of the UASB reactors were high, ranging from 17 to 21 mg.L-1 and from 7 to 11 mgS.L-1, respectively. Losses of dissolved methane in the effluent of UASB were higher than 30% of all methane formed inthe reactor, confirming that losses of energy potential due to methane dissolution in the effluent are very significant. Moreover, the removal of gaseous constituents through the influence region of the settler surfaces of the UASB reactors was very small, with a large portion of the methane and sulfide still remaining dissolved in the liquid effluent. Massbalances were performed and indicated the following ranges: i) for the COD balance: soluble effluent (14-24%), washout sludge (10-20%), retained sludge (8-10%), CH4 biogas (24-30%), dissolved CH4 (16-18%), sulfate reduction (4-5%); and ii) for the sulfur balance: effluentsulfate (15-18%), sulfide effluent (57-64%), precipitated sulfide in the retained sludge (3-5%), absorbed sulfide for the cells in the retained sludge (4-5%), precipitated sulfide in the washout sludge (2-4%), absorbed sulfide for the cells in the washout sludge (2-5%), sulfide in thebiogas (1%). Finally, it was concluded that a single unit after the reactor like a dissipation chamber can be able to remove dissolved methane and sulfide in the order of 40%. If optimized this type of unit can likely to have an even greater efficiency.